YQHX Alleviates H/R-Induced Cardiomyocyte Apoptosis by Downregulating miR-1. (2nd November 2021) - Ge, Luandie; Fan, Yaqi; Fu, Lin; Guo, Mengjiao; Cao, Panxia; Peng, Chaojie; Wu, Linke; Han, Lihua; Wu, Hong
Abstract : Yiqi Huoxue granule (YQHX) inhibits cardiomyocyte apoptosis in myocardial ischemia-reperfusion injury (MIRI); however, the underlying mechanism is unknown. In this study, hypoxia-reoxygenation (H/R) models were established using rat myocardial primary cells and H9c2 cells, lactate dehydrogenase (LDH), and creatine kinase (CK) levels and cardiomyocyte apoptosis were determined. LDH release, CK activity, caspase-3 activation, mRNA and protein ratio of Bax/Bcl-2, and miR-1 expression were significantly higher (p < 0.01 ) in the H/R model of rat myocardial primary cells and H9c2 cells compared with the control group and was inhibited by YQHX treatment (p < 0.01 or p < 0.05 ). We also found that miR-1 overexpression could enhance apoptosis in cardiomyocytes, whereas apoptosis could be reduced by YQHX treatment (p < 0.01 ). In conclusion, YQHX alleviates H/R-induced cardiomyocyte apoptosis by inhibiting miR-1 expression, suggesting the potential of YQHX in preventing MIRI.